2005
DOI: 10.1007/s11274-005-0079-9
|View full text |Cite
|
Sign up to set email alerts
|

Lactase Production from Lactobacillus acidophilus

Abstract: A lactobacillus strain isolated from fermented Ragi (Eleusine coracana Gaertn.) was characterized as Lactobacillus acidophilus. The isolate was found to be homofermentative, slime-forming and a lactase (b-galactosidase) producer. Production, recovery, characterization and performance of lactase were studied at laboratory scale from 100 ml to 5 l under stationary and stirred conditions. 1.5% lactose was found to be the best carbon source for lactase production. The lactose content could be reduced to 0.75% by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Indigenous L. acidophilus isolated from fermented ragi was used in the present study (Akolkar et al 2005). This isolate was grown in 50 mL MRS broth in 250-mL Erlenmeyer flask and incubated at 37°C under stationary conditions.…”
Section: Microorganisms and Its Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Indigenous L. acidophilus isolated from fermented ragi was used in the present study (Akolkar et al 2005). This isolate was grown in 50 mL MRS broth in 250-mL Erlenmeyer flask and incubated at 37°C under stationary conditions.…”
Section: Microorganisms and Its Maintenancementioning
confidence: 99%
“…In our previous study, we have isolated a Lactobacillus acidophilus strain from fermented ragi (Eleusine coracana), found to be a potential β-galactosidase producer (Akolkar et al 2005(Akolkar et al , 2006. Since the strain was isolated from ragi, one would expect the microbial isolate to possess specific enzymatic characteristics in the carbohydrate metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Because we thought that the enzyme from Rahnella aquatilis 14-1 may be a novel type of β-galactosidase, we attempted to purify this respective enzyme the purification of the enzyme was conveniently done by chromatography, using Sephadex G-25 and DEAE-cellulose columns, which is often used for the purification of β-galactosidase (Hoyoux et al 2001;Fernandes et al 2002;Turkiewicz et al 2003;Akolkar et al 2005). The enzyme was purified until a single band had been obtained in 10% SDS-PAGE, which corresponded to a molecular mass of cca 60 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with previous studies in which the presence of lactose in media enhanced β-gal activity when compared to the presence of glucose. We found that the presence of lactose in the growth medium led to β-gal activity enhancement for bifidobacteria and L. acidophilus specifically, [11,12]. We also examined the effect of bile on β-gal activity and found an increase in enzyme activity when bile was included in the medium (Table 2).…”
Section: β-Gal Of Probiotic Supplements After Exposure To 3% Bile (W/v)mentioning
confidence: 93%